الجامعة الإسلامية الحكومية بنجكولو - Ernawati Ernawati (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
Language is a means of cultural preservation. A culture will be able to be understood and upheld by the recipients of the culture if they understand the language of the culture. It is often thought that culture is born out of language, without language there can be no culture.Even so it turns out the language of a society was very influenced by the culture of society. In semantic analysis, Abdul Chaer said that the language is unique and has a very close relationship with the culture of the wearer community, then a language analysis only applies to that language only, it can not be used to analyze other languages. For example in the culture of British society who do not know rice as staple food there is only the word rice to declare nasi, beras, gabah, and padi. So, the word rice in English refers to kepada nasi, beras, gabah, and padi in Indonesian. Variations in the Indonesian language is due to the proximity of Indonesian society with rice as a staple food which is a form of Indonesian society culture